Analysis of Food Geopolitical Threats to Food Sustainability in East Kalimantan: Challenges, Obstacles and Discourse on Food Sustainability Resilience - Rofik, Abdul; Pratama , Prawira Yudha; Nurain, Intan; Rahman , Taufik (Manunggal Halim Jaya, 2024)
An Analysis of Food Geopolitical Threats to Food Sustainability in East Kalimantan reveals the significant impact of global geopolitical dynamics on food availability and market prices at the local level. The Russia-Ukraine war and the U.S.-China trade war are decisive factors affecting the dependence of Indonesia, especially East Kalimantan, on food imports from certain countries such as India, Thailand, Vietnam and Pakistan. Vulnerability to fluctuations in global food markets creates serious challenges to food stability at the local level. Challenges and constraints to food security in East Kalimantan Province include climate change, land conversion, extreme weather variability, deforestation, river pollution and social conflict. These factors threaten agricultural productivity and point to the need for mitigation efforts. Lack of agricultural infrastructure, poor transportation access, and farmers' limited access to modern agricultural technology and knowledge are also major obstacles that need to be overcome. In an effort to maintain food security, the local government has taken strategic steps, including a commitment to suppress land conversion and strengthen agricultural areas. The 2021-2026 Regional Medium-Term Development Plan (RPJMD) shows the government's commitment to achieving these goals. However, this sustainability must be implemented seriously, as failure could trigger conflicts between stakeholders such as local farmers, mining companies and local governments. The importance of sustainability in the context of food security in East Kalimantan is illustrated by the government's efforts in preparing the archipelago's capital region as a place for massive food production. Conventional and urban farming approaches utilizing modern agricultural technology show the seriousness in finding sustainable solutions. To overcome challenges and prevent conflicts, serious and comprehensive cooperation between the government, local farmers and the industrial sector is needed. Sustainability of food security requires sustainable policy implementation, investment in agricultural infrastructure, and empowerment of farmers. This will have a positive impact on the socio-economic stability of the community and minimize the potential for conflict at the local level such as East Kaliamantan and ensure political and economic stability at the local level.